2019
DOI: 10.1016/j.neulet.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-intensity electrical stimulation and adipose derived stem cells transplantation on the time-domain analysis-based electromyographic signals in dogs with SCI

Abstract: Low-intensity electrical stimulation and adipose derived stem cells transplantation on the time-domain analysis-based electromyographic signals in dogs with SCI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Functional electrical stimulation has not yet been reported in dogs, but a wearable device is being developed that might be useful in dogs with incomplete recovery from acute IVDH (80). Short-term, low-intensity electrical stimulation of the spinal cord with or without stem cell transplantation has been performed in chronically paraplegic dogs (81). While electromyographic changes in pelvic limb muscles implied improvement in motor conduction, further investigation would be necessary to optimize therapy and determine if there is a clinical benefit (81).…”
Section: Functional Electrical Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional electrical stimulation has not yet been reported in dogs, but a wearable device is being developed that might be useful in dogs with incomplete recovery from acute IVDH (80). Short-term, low-intensity electrical stimulation of the spinal cord with or without stem cell transplantation has been performed in chronically paraplegic dogs (81). While electromyographic changes in pelvic limb muscles implied improvement in motor conduction, further investigation would be necessary to optimize therapy and determine if there is a clinical benefit (81).…”
Section: Functional Electrical Stimulationmentioning
confidence: 99%
“…Short-term, low-intensity electrical stimulation of the spinal cord with or without stem cell transplantation has been performed in chronically paraplegic dogs (81). While electromyographic changes in pelvic limb muscles implied improvement in motor conduction, further investigation would be necessary to optimize therapy and determine if there is a clinical benefit (81). Additionally, there is experimental evidence and data in dogs with naturally-occurring injury for electrical stimulation of peripheral nerves or nerve roots to aid in restoration of urination and defecation (82)(83)(84).…”
Section: Functional Electrical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [31] performed electroacupuncture on rats with spinal cord injury and found that this treatment is effective to prevent oligodendrocyte apoptosis and to improve functional recovery after spinal cord injury. Krueger et al [32] performed the association of electrostimulation with mesenchymal stromal cells derived from adipose tissue in dogs with SCI and observed improvement, but without statistical difference between the associated treatments (electrostimulation and MSCs) and isolated.…”
Section: Treatmentsmentioning
confidence: 99%
“…Intralimb hip–knee coordination may be promoted by the combination of FES and locomotor training [ 37 , 38 , 39 ]. In chronic patients, electrical stimulation protocols with FES and Transcutaneous Electrical Spinal Cord Stimulation (TESCS) could be applied as a possible therapeutic neurorehabilitation tool for IVDD [ 40 , 41 , 42 , 43 ]. TESCS can lead to synergistic and interactive multi-segmental effects, converging with the ascending sensorial pathways and the descending motor pathways, that might be important in activating the spinal network [ 44 ].…”
Section: Introductionmentioning
confidence: 99%